The historian in the pandemic: what has been done about the history of nonconventional medicine in epidemics? - Waisse, Silvia (Circumscribere International Journal for the History of Science, 2021)
From governments to the general public, one may ask about the possible contributions of historians, if any, to the understanding and management of global disasters, as e.g. the ongoing coronavirus disease 2019 (COVID-19). Given the confuse situation at the onset of the pandemic in terms of diagnosis, treatment, and prevention, a look into past experience with nonconventional medicine seemed relevant. In the present study I surveyed secondary literature on the role of Chinese medicine, Āyurveda, and homeopathy over time. The quantitative results were disappointing: nothing on Āyurveda, and one single study each on Chinese medicine and homeopathy. The quality of the former compensates for the numerical short age. The case of homeopathy is rather sui generis, since this medical system was born and blossomed during epidemics and pandemics. I conclude with a short comment on reference sources, which might serve as point of departure for future studies of Āyurveda in epidemics.